Portrait of Jöns Jacob Berzelius - Krüger, Franz (Wilhelm Engelmann)
Jöns Jacob Berzelius (1779 - 1848) was a Swedish physician, chemist, and one of the founders of modern chemistry. He is particularly recognized for determining atomic weights in his experiments, which contributed to a more comprehensive understanding of stoichiometry. This principle is known today as the "Law of Constant Proportions." Berzelius was additionally a member of the Royal Swedish Academy of Sciences.
Keywords: Berzelius, Jöns Jakob, friherre, 1779-1848; Portraits